Beyond the chimarrão: the influence of FOMO (fear of missing out) on conspicuous consumption among gauchos - Oliveira, Larissa Gusmão; Gundlach, Gabriela Noetzold; Corso, Kathiane Benedetti (Revista de Administração da UFSM, 2025)
Purpose: This study delves into the impact of fear of missing out on conspicuous consumption practices among gaucho consumers. Conspicuous consumption refers to the ostentatious display of wealth and possessions to achieve social status, while the fear of missing out is the anxiety associated with missing out on social experiences or events. Design/methodology/approach: To examine this relationship, an online survey was conducted with 389 individuals residing in Rio Grande do Sul, Brazil. The survey, administered through Google Forms, comprised four sections utilizing a five-point Likert scale. Findings: Data analysis employed descriptive statistics and simple linear regression. The findings revealed a significant positive correlation between the fear of missing out and conspicuous consumption behaviors. This indicates that the fear of missing out plays a substantial role in influencing consumers’ purchasing decisions, steering them towards acquiring products that signal status and social affiliation. These insights underscore the importance of understanding the fear of missing out within the context of conspicuous consumption. Originality: By recognizing this connection, marketers can devise targeted strategies that resonate emotionally with consumers and effectively influence their purchasing choices.